Analysis of Emotion Frequency in the Texts of Kazakh and Tuvan Literature - Mansurova, Elnara Zh.; Orda, Gulzhakhan Zh.; Askarova, Gaukhar S. (The New Research of Tuva, 2025)
The article presents a comparative content-contextual analysis of emotional expressions in two literary works — the novella “A Childhood That Never Happened” by Kazakh writer Akberen Elgizhek and the novella “The Story of the Bright Boy” by Tuvan writer Stepan Saryg-ool, both examined in their Russian-language literary translations. The study is based on a corpus analysis of the texts, which enables the identification of the frequency of key emotions (“fear”, “sadness”, “joy”, “sorrow”, and “anger”) and their contextual meanings. In the Tuvan novella, there is a predominance of the lexemes “fear” and “sadness”, indicating an open and explicit mode of emotional representation. In contrast, in the Kazakh novella, emotions such as “joy”, “fear”, and “sorrow” are more often conveyed implicitly, through context and artistic imagery. The findings of the study demonstrate that emotional vocabulary in Tuvan prose tends to express feelings in a more direct and explicit manner, while in Kazakh prose, emotions are more frequently communicated through poetic imagery and contextual nuances. This distinction is rooted in national storytelling traditions and cultural conventions of emotional perception.